A scoping review of the integration of empowerment-based perspectives in quantitative intersectional stigma research. Issue 8 (3rd August 2022) - Logie, Carmen H.; Earnshaw, Valerie; Nyblade, Laura; Turan, Janet; Stangl, Anne; Poteat, Tonia; Nelson, LaRon; Baral, Stefan
ABSTRACT: The genesis of the concept of intersectionality was a call to dismantle interlocking systems of oppression – racial, sexual, heterosexual, and class-based – in order to realise liberation of Black women and other women of colour. Intersectionality holds the radical potential to amplify collective efficacy, community solidarity, and liberation. The extension of intersectionality into stigma research has resulted in an increased focus on intersectional stigma in quantitative research. This raises questions regarding how the radical and liberatory potential of intersectionality is applied in stigma research. Specifically, empowerment-based perspectives may be overlooked in quantitative intersectional stigma research. We conducted a scoping review to document if and how empowerment-based perspectives were included in intersectional stigma quantitative studies. We identified and included 32 studies in this review that examined varied stigmas, most commonly related to race, gender, HIV and sexual orientation. In total 13/32 (40.6%) of these studies reported on empowerment-based factors; most of these examined social support and/or resilience. Taken together, findings suggest that the quantitative intersectional stigma research field would benefit from expansion of concepts studied to include activism and solidarity, as well as methodological approaches to identify the protective roles of empowerment-based factors to inform health and social justice-related programmes and policy.